Beginning Smartphone Web Development - Frederick, Gail Rahn (Apress, 2012)
I believe in the W3C’s principle of One Web—that services and information on the web should be thematically consistent and accessible to all kinds of devices, without regard to differences in presentation capabilities. Informally, the One Web principle means that if I write my grocery list online at home in Firefox, I should be able to view the list and check off my purchases at the grocery store using my mobile phone. That said, the Mobile Web and its ecosystem are unique in many ways—in access patterns, user behaviors, browser technologies, and client capabilities. A recent mobiThinking report coined the maxim “utility is the engine of the Mobile Web”. This phrase has become my mantra for Mobile Web development and I encourage you to adopt it as well. Mobile Web content succeeds when it solves a real problem for a user on the move. Driving directions, public transportation, business listings, news headlines, social networking, and banking are all examples of content that succeeds on the Mobile Web because real people using mobile phones in their daily lives find this information to be relevant, local, and immediately available.